JARINGAN SOSIAL UMKM MPOK SINAH KLAMBEN DI KELURAHAN MANGKUBUMEN SURAKARTA - Faiz, Muhammad (Jurnal Ilmiah Sosiologi Agama (JISA), 2025)
Surakarta is one of the most popular tourist destinations in Indonesia, especially because of its culinary specialities such as gudeg ceker, tengkleng kambing and nasi liwet, which are mostly managed by MSMEs engaged in the culinary field. This study aims to identify the formation of social networks and analyse the embeddedness between Micro, Small and Medium Enterprises (MSMEs) and consumers in supporting business sustainability in the Mpok Sinah Klamben community, Mangkubumen Village, Surakarta. The purpose of this study is to identify the formation of social networks and analyse the embeddedness between MSME actors and consumers in business continuity. The research method used is a qualitative approach with a case study, data collected through observation and interviews from eight informants selected by purposive sampling. The results showed that social networks are formed through five main stages: initiation, participation, strengthening between actors, expansion, and institutionalisation. Intensive interaction between MSME actors, relational embeddedness with consumers, and the role of managers as facilitators strengthen business sustainability in the area. This research analyses social networks using Mark Granovetter's theory, especially on aspects of network norms and density, strength of weak ties, structural holes, and embeddedness. The theoretical contribution of this research lies in strengthening the understanding of the importance of social embeddedness in local community-based microeconomic networks. Practically, the findings can serve as a reference for managers and local governments in designing strategies to strengthen community-based MSMEs through social network optimisation.